Use of statistical tools for verification and control of the isotopic enrichment process of uranium hexafluoride enriched to a maximum of 5% of 235U (Research, Society and Development, 2020)
This article aims to use statistical tools to verify the behavior and control the isotopic enrichment process of uranium hexafluoride enriched to a maximum of 5% of 235U. Analyze the behavior of the process as well as the establishment of a statistical method to monitor and control production in order to increase productivity and decrease costs. The methodology used for the development of this work were the fundamentals related to descriptive statistics such as the Anderson-Darling normality test, verification of average and pattern deviation as well as graphs of histogram, probability and individual content values, in addition to the boxplot analysis. for two different enrichment campaigns.